Growth, photosynthetic function, and stomatal characteristics of Persian walnut explants in vitro under different light spectra - Saeedi, Seyyed Arash; Vahdati, Kourosh; Sarikhani, Saadat; Daylami, Shirin Dianati; Davarzani, Maryam; Gruda, Nazim S.; Aliniaeifard, Sasan (Frontiers in Plant Science, 2023)
Light plays a crucial role in photosynthesis, which is essential for tissue culture and ex vitro acclimatization. LED lights are an appropriate technology for in vitro lighting but their effect on propagation and photosynthesis is not well comprehended. This study aimed to investigate the impact of different light spectra on the growth, photosynthetic functionality, and stomatal characteristics of micropropagated shoots of Persian walnut (cv. Chandler). Tissue-cultured walnut nodal shoots were grown under white, blue, red, far-red, green, a combination of red and blue (70:30), a combination of red and far-red (70:30), and fluorescent light as a control. The research found that the best growth and vegetative characteristics of in vitro explants of Persian walnut were achieved under a combination of red and blue light. The research also observed that the red spectrum light treatments stimulated stomatal closure, while the stomatal size of walnut explants was controlled under blue and white spectrum treatments and caused stomatal opening. The research found that although the red and far-red light spectrum resulted in the formation of elongated explants with more lateral shoots and anthocyanin content, it significantly reduced the photosystem II efficiency. The highest Fv/Fm and the highest soluble carbohydrate content were found in explants grown under blue and white spectra. In conclusion, according to this research, combining red and blue light leads to better growth, photosynthesis functionality, and the emergence of functional stomata in in vitro explants of Persian walnuts.